Long-Term Results after Diversion Surgery in Extrahepatic Portal Vein Obstruction - Triana Junco, Paloma; Alvarez, Ana; Dore, Mariela; Jimenez Gomez, Javier; Sánchez Galán, Alba; Vilanova-Sánchez, Alejandra; Andres, Ane; Encinas, Jose Luis; Martinez, Leopoldo; Hernandez, Francisco; Lopez Santamaria, Manuel (European Journal of Pediatric Surgery, 2019)
Aim Extrahepatic portal vein obstruction (EHPVO) is a frequent cause of noncirrhotic portal hypertension in children. The aim of this study is to analyze long-term results after diversion surgery.Patients and Methods Retrospective review of EHPVO patients who underwent diversion surgery analyzing number of platelets, leukocytes, prothrombin activity, splenomegaly, and gastrointestinal bleeding 10 years after surgery.Results Thirty-three patients were evaluated, mostly males (64%) and presenting with gastrointestinal bleeding (46%). Mesoportal shunt (Rex) was performed in 19 patients, mesocaval in 7, distal splenorenal in 7, and proximal splenorenal in 3. While comparing mesoportal shunt to the other portosystemic shunts, an increase in platelets was found with every technique, but it was clearly higher in mesoportal shunt. The highest increase was 6 months after surgery (p = 0.0015) as well as prothrombin activity (p = 0.0003). Leukocytes level also increased without statistical significance. Spleen size (cm) and spleen size Z score (SSAZ) decreased significantly 6 months after mesoportal shunt (p = 0.0168). Before surgery, over 94% patients suffered gastrointestinal bleeding, which reduced significantly afterward with bleeding episodes in only four (12%) of them.Conclusion Diversion surgery in EHPVO, especially mesoportal shunt of Rex, improves hepatic function (prothrombin activity), reduces hypersplenism (platelets, leukocytes, and spleen size), and decreases gastrointestinal bleeding episodes.
Keywords: extrahepatic portal vein obstruction; diversion surgery; shunt Rex; children